'Why nurses are leaving the profession … lack of support from managers': What nurses from an e‐cohort study said. Issue 4 (26th February 2014) - Tuckett, Anthony; Winters‐Chang, Peta; Bogossian, Fiona; Wood, Michael
<x xml:space="preserve">Abstract</x> The shortage of nurses is known. We explored nurses' reasons for leaving the profession based on responses from an e‐newsletter of the Nurses and Midwives e‐cohort Study. Qualitative content analysis of data from email responses (n = 66) showed 'Lack of support' as a social work value describing their manager's lack of support, unsupportive relationships within their work group, and a health‐care system putting business principles before care resulting in job dissatisfaction and nurse turnover. These findings are examples of a 'complex'/'wicked' problem and as such will resist simple solutions to the presenting issues. The dialogic process such as Open Space Technology and Talking Circles should be considered as potentially suitable to the needs of nurses.